Penerapan Media Scratch untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Kelas V pada Materi Rantai Makan - Abduh, Muhammad; Maftuh, Ade; Zulkarnaen, Rizki Hadiwijaya (Indo-MathEdu Intellectuals Journal, 2025)
This research is a Classroom Action Research (CAR) which aims to improve problem-solving skills in Natural and Social Sciences (NSS) subjects on the Food Chain through Scratch media in class V of SDN Bojongsari, Leuwisari District, Tasikmalaya Regency. The research was conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The subjects in this study were 32 class V students. Data collection techniques used included observation, testing, and documentation. The results of the study showed an increase in students' problem-solving abilities from pre-action to cycle I and cycle II. The average score of students in pre-action was 66.09 with a completion of only 31.25%. After the application of Scratch media, the average score in cycle I increased to 78.62 with a completion of 53.12%, and in cycle II it increased again to 83.56 with a completion of 78.12%. These results indicate that the application of Scratch media can effectively help students understand the concept of Food Chains and improve problem-solving abilities. Thus, it can be concluded that the application of Scratch media can be an alternative effective learning media in improving students' problem-solving abilities in the Food Chain material in elementary schools.